L’ubi consistam delle scienze sociali - Michela Luzi (Culture e Studi del Sociale)
The Social sciences will have to ensure that the contemporary individual, often alone, misfit and bored by the banality of everyday life, is able to reappropriate that Ubi Consistam, that can only be sought and founded only through one's own life and the “Individual law”. The prevailing, the resignation, the paralysis or the laziness in the individual must not prevail, because this would favor the utilitarianism and economicism that characterize contemporary society. It is necessary to reactivate the desire to grasp, feel, perceive its fundamental unity and multiplicity in research, trying to safeguard and reactivate their emotional heritage.